DETERMINING FACTORS OF CASH WAQF ONLINE ON KITABISA.COM CROWDFUNDING PLATFORM - Alya Azhaar (JURNAL STUDI MANAJEMEN ORGANISASI, 2022)
The research is to describe the effect of religiosity, cash waqf literacy, subjective norms, and trust in distributing cash waqf online on the Kitabisa.com online platform. This research is a descriptive quantitative research. The samples are the users of Kitabisa.com who had distributed their money for cash waqf. The data collection method was carried out by distributing questionnaires to 100 respondents. The analytical method used is descriptive analysis. While statistical analysis uses multiple linear analysis techniques with data testing using the SPSS Statistics 25 program. The results show that partially cash waqf literacy, subjective norms, and trust have an effect on waqf decisions in cash waqf through the Kitabisa.com platform. While partially religiosity has no effect on wakif decisions in cash waqf through the Kitabisa.com platform. While simultaneously religiosity, cash waqf literacy, subjective norms, and trust have a positive effect on waqf decisions in cash waqf through the Kitabisa.com platform.